2013
DOI: 10.1016/j.phymed.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A diarylheptanoid phytoestrogen from Curcuma comosa, 1,7-diphenyl-4,6-heptadien-3-ol, accelerates human osteoblast proliferation and differentiation

Abstract: Curcuma comosa Roxb. is ginger-family plant used to relieve menopausal symptoms. Previous work showed that C. comosa extracts protect mice from ovariectomy-induced osteopenia with minimal effects on reproductive organs, and identified the diarylheptanoid (3R)-1,7-diphenyl-(4E,6E)-4,6-heptadien-3-ol (DPHD) as the major active component of C. comosa rhizomes. At 1–10 μM, DPHD increased differentiation in transformed mouse osteoblasts, but the effect of DPHD on normal bone cells was unknown. We examined the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Previously, we reported that E2 promotes osteoblast proliferation via activating the MAP kinase activity. (18) In this study, we investigated the effect of S1P on the MAP kinase activity in osteoblast precursors (h-MSC) and osteoblasts (hOB). S1P-stimulated phospho-AKT and phospho-ERK at 15 minutes in h-MSC are shown on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that E2 promotes osteoblast proliferation via activating the MAP kinase activity. (18) In this study, we investigated the effect of S1P on the MAP kinase activity in osteoblast precursors (h-MSC) and osteoblasts (hOB). S1P-stimulated phospho-AKT and phospho-ERK at 15 minutes in h-MSC are shown on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other experimental models, ASPP 049 has been shown to exert anti-inflammatory action and beneficial effects on bone density and cholesterol levels acting via estrogen receptors. [14,16,21]. Astroglial cell death induced by H 2 O 2 was found to be accompanied by elevation of intracellular ROS indicating the presence of oxidative damage.…”
mentioning
confidence: 94%
“…This is well documented in contexts including estrogen and synthetic estrogen receptor modifier response of human osteoblasts. 35 In regard to this, when studied in vivo , modification of the rate of osteoblast differentiation is largely masked, with bone appearing to develop and mineralize normally, but with differences in the rate of bone formation under some circumstances, and differences in the susceptibility of bone to regional necrosis 36 when survival signals including VEGF 1 are compromised. In this regard, sensitization of osteoblast VEGF production to ACTH by 1,25(OH) 2 D deserves further study and might be useful in clinical trials in contexts including glucocorticoid treatment where osteonecrosis is commonly seen.…”
Section: Discussionmentioning
confidence: 99%